Formation of the protective potential of underground steel pipelines in the context of the development of modern converter technologies - Aziukovskyi O.; Shykhov S. (НТУ "ДП", 2024)
Goal. To study the processes of forming the protective potential of underground steel pipelines in the face of the development of modern converter technologies. To evaluate the influence of the output signal parameters of cathodic protection rectifiers on the electrochemical protection of steel underground pipelines. Мета. Дослідити процеси формування захисного потенціалу підземних сталевих трубопроводів в умовах розвитку сучасних перетворювальних технологій. Оцінити вплив параметрів вихідних сигналів випрямлячів катодного захисту на електрохімічний захист сталевих підземних трубопроводів.
Формування захисного потенціалу підземних сталевих трубопроводів в умовах розвитку сучасних перетворювальних технологій
Keywords: cathodic protection; underground steel pipelines; impedance; rectifiers; electrochemical protection; spectrum; катодний захист; підземні сталеві трубопроводи; повний опір; випрямлячі; електрохімічний захист; спектр